Relevansi Nilai Dividend Yield dan Price Earnings Ratio dengan Moderasi Investment Opportunity Set (IOS) dalam Penilaian Harga Saham - I Ketut Jati (The Indonesian Journal of Accounting Research, 2013)
This study develops and tests a market valuation model whose main prediction is that equity value is a function of book value, earnings, and dividend. This function is extended by using relative level of investment opportunity set (IOS) as a moderation variable. The using of IOS level is aimed to search value relevance of dividend yield and price earnings ratio (PER) commonly used in market price valuation. As model used in this study, dividend and retained earning has reflected the use of dividend yield and PER by market participants.Samples used in this study are selected using purposive sampling from public companies of Jakarta Stock Exchange (BEJ) from 1993 to 1996. Based on model used, the results show that book value, retained earnings, and dividend have relation to stock price or they have value relevance. By adding relative level of IOS as a moderation variable in this functional relation, value relevance of dividend yield is more related to a high IOS companies. Companies in a high IOS show that dividend yield and PER have value relevance. Companies in a high IOS are more related to dividend yield than PER. These results are different from Riahi-Belkaoui and Picur (2001) research that shows companies in a low IOS tend to “dividend yield valued,” and companies in a high IOS tend to “PE valued.”